2015
DOI: 10.1080/15438627.2015.1040917
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Minimalist Footwear on Knee and Ankle Load during Depth Jumping

Abstract: Plyometric training is used by athletes to promote strength and explosive power. However plyometric activities such as depth jumping are associated with a high incidence of injuries. This study examined the influence of minimalist and conventional footwear 10 on the loads experienced by the patellofemoral joint and Achilles tendon. Patellofemoral and Achilles tendon forces were obtained from ten male participants using an eight -camera 3D motion capture system and force platform data as they completed depth ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
1
10
1
1
Order By: Relevance
“…The first key finding from the current investigation is that peak hip and knee joint forces were shown to be significantly larger in the minimalist in comparison to conventional footwear. This observation opposes the findings of Sinclair et al [23], who found that minimalist footwear reduced the specific loads experienced at the patellofemoral joint. It is proposed that this divergence relates to the distinct nature of the loading patterns associated with the two knee joint articulations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The first key finding from the current investigation is that peak hip and knee joint forces were shown to be significantly larger in the minimalist in comparison to conventional footwear. This observation opposes the findings of Sinclair et al [23], who found that minimalist footwear reduced the specific loads experienced at the patellofemoral joint. It is proposed that this divergence relates to the distinct nature of the loading patterns associated with the two knee joint articulations.…”
Section: Discussioncontrasting
confidence: 99%
“…They showed that in minimalist footwear, average and instantaneous loading rate were significantly lower but that jump height was also significantly reduced. Finally, Sinclair et al [23] examined the effects of minimalist and conventional footwear on patellofemoral and Achilles tendon loads during the depth jump. Their findings showed that whilst no differences were evident in Achilles tendon kinetics, minimalist footwear significantly reduced patellofemoral loading.…”
Section: Introductionmentioning
confidence: 99%
“…Of further importance is the finding that peak ankle loads were significantly greater in the minimalist footwear in comparison to the squash specific and running shoe conditions. This observation also concurs with the findings of Sinclair (2014) and Sinclair, et al (2015c) who showed in runners that ankle loading was significantly larger when wearing minimalist footwear in comparison to conventional athletic trainers. It is proposed that this observation relates to the increase plantarflexion moment contribution observed in minimalist footwear as no differences in ankle angle were shown between footwear.…”
Section: Ankle Loadssupporting
confidence: 92%
“…Many athletic shoes possess a raised heel with respect to the forefoot (i.e. pitch) – a feature that has been previously shown to increase peak KFM compared to barefoot in adult runners [ 11 , 12 , 24 ]. Given that high-supportive shoes often have an increased pitch compared to their low-supportive counterparts, it’s imperative that an examination of high-support footwear includes an analysis of frontal, transverse and sagittal plane knee moments (i.e., KAbM, KIRM and KFM) as many late/post-pubertal girls are likely wearing these types of shoes while playing sport.…”
Section: Introductionmentioning
confidence: 99%